EVALUATION OF HEPATOPROTECTIVE ACTIVITY OF VERNONIA CINEREA (L.) LESS AND CUMINUM CYMINUM IN CARBON TETRACHLORIDE INDUCED LIVER DAMAGE IN RATS - A. NISHADH (International Journal of Pharma and Bio Sciences, 2013)
The present study deals with the effect of herbal powder of Vernonia cinerea and Cuminum cyminum on tissue defense system against CCl4 (carbon tetrachloride) induced hepatic injury in rats. CCl4 diluted with liquid paraffin oil (1:1 ratio) in a dose of 1ml / kg body wt was given intraperitoneally for 2 days. Herbal powder as a suspension of water (10mg / 100g body wt / day) was administered orally for 15 days to rats intoxicated with CCl4. Induction with CCl4 resulted in an increase in the levels of aspartate transaminases, alkaline phosphatase, alanine transaminases and total bilirubin in serum. Post treatment with herbal powder reversed the deleterious effects of CCl4 and the enzymes were found to be near normal. These findings demonstrate the protective nature of herbal powder against CCl4 induced liver damage.